Income Tax Regulations for Child Content Creators of TikTok Platform: Inefficacy of Indonesian Legal Frameworks - Wulandari, Dinda Agustin; Jaelani, Abdul Kadir; Victoria, Ong Argo (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2024)
The massive growth of social media opens the door for anyone gain a lucrative content broadcasting which in turn benefit the subject in economic capacity and later becomes a potential of taxation object. However, not all content creators are subjected to income tax, such as the minors. The imposition of income tax must consider the subjective requirements which is related to the age of the tax subject. This study aims to examine the efficacy of Indonesian legal norms as a basis for imposing taxes on child content creators who have income above the minimum tax threshold. This research employs a statute approach completed with comparative perspective. Data were collected by investigating tax regulations in Indonesia and then comparing them with tax regulations in other countries. This study finds that income tax for minors is actually mentioned in Indonesian legislation. However, these regulations do not explicitly stipulate that children bear the responsibility for their own income tax. The law stipulates that the payment of a child's income tax integrates with their parent’s tax payment. This circumstance is different from the advanced countries like the USA and Australia where regulations regarding children's income tax are specifically addressed. Consequently, in Indonesia, minor content creators who have high incomes cannot be unequivocally subjected to income tax. This is because minors cannot obtain a Taxpayer Identification Number (NPWP) in their own name. For children with an economic capacity exceeding the minimum income threshold, obtaining a Taxpayer Identification Number is not mandatory.